Caracterização de reservatórios carbonáticos do campo de Berbigão, Pré-Sal Brasileiro: avaliação de formações e inversão sísmica - Barbosa, Thiago Henrique da Silva (2024)
The carbonate reservoirs of the Brazilian Pre-salt have unique characteristics in terms of texture and sedimentological processes. These specific properties significantly increase the degree of uncertainty that this type of depositional environment presents compared to other systems. In addition to their complexity, the reservoirs in this province are currently the country's main fossil energy asset and account for approximately 78.5% of all the oil produced in the country. Therefore, a detailed evaluation of the different carbonate petrophysical constrains of the Barra Velha Formation is necessary to understand how the characteristics of accumulation and flow in porous media are distributed in the subsurface. This study aimed to measure the main factors affecting the quality of Pre-salt carbonate reservoirs and to explain their control on the permoporous and acoustic properties in the area covered by Berbigão oilfield. To carry out this analysis, we used an integrated approach based on 3D seismic data, well logs, dynamic tests and core data (RCAL and SCAL) from two wells in the Berbigão oilfield, Santos Basin, in the Barra Velha Formation. The results show a substantial difference in petrophysical and 3D acoustic properties between the two mound alignments in the Berbigão oilfield. While the secondary mound observed in the well and impedance sections is dominated by high clay contents and a predominance of microporous facies, the main mound displays dissolution features and large dissolution features that control fluid flow and exhibit high excess permeabilities. It is also clear that it is challenging to correctly characterize the producing zones without dynamic data since the synergetic matrix-fracture coupling governs the flow behavior. The interpretation of well tests and the integration of production logs allowed the comparison between static interpretation and the productivity of the producing zones, as well as the investigation of zones of interest at a reservoir-scale. These correlations regarding the control of petrophysical characteristics were also observed in the acoustic impedance, obtained from the quantitative seismic interpretation workflow, which enabled three-dimensional inferences on spatial heterogeneity aspects. This study integrates data at different scales into a comprehensive analysis of the heterogeneities that occur in the Brazilian Pre-salt reservoirs, improving knowledge of the study area and the crucial factors for characterizing the reservoirs of the Barra Velha Formation.